The Development of Classroom Attendance System: Case Study Faculty of Informatics, Mahasarakhan University - Chottanom, Anirut (Journal of Applied Informatics and Technology, 2021)
Check the list of attendance performs the interaction between teachers and students. There are many additional benefits to the classroom, such as encouraging class members’ attendance to the classroom, gaining the behavior score, and making class members know each other. It is helpful to check the list of members in the classroom. Although, it wastes time in teaching, especially checking the list of members in the large classroom, for example, general education courses and introductory courses of each department. Nowadays, many teachers still record their attendance on paper. These may cause delays while processing the attendance data, sometimes loss the attendance data and deterioration. It is also difficult for students to check their classroom attendance. In this research, we proposed using information technology to help teachers to check the list of students in the Faculty of Informatics, Mahasarakham University. The classroom attendance system could address the problems mentioned above. The proposed classroom attendance system was designed using responsive web technology. This system 1) allowed students to attend the classroom themself by using their smartphones and 2) allowed teachers to use the system to check the list of students. When teachers use the system to check classroom attendance, it benefits the students who do not have smartphones and have no internet connection on their smartphones. The proposed classroom attendance system could report the classroom attendance statistics in the numeric format and dashboard style. We then measure the satisfaction of users of the proposed classroom attendance system using a questionnaire. The satisfaction scale was measured at level 5. The results showed that The teachers’ satisfaction with the system was at the highest level of satisfaction. The mean satisfaction value was 4.26 and a standard deviation value of 0.76. For the students, we found that the satisfaction level was very satisfactory. The average satisfaction value was 4.12, a standard deviation value of 0.79.